Bridging the gap between conservation delivery and economics with precision agriculture - Mark D. McConnell (Wildlife Society Bulletin)
ABSTRACT Agricultural landscapes are important for natural resource conservation, but present numerous obstacles associated with intensive agricultural production. Chief among these challenges is the competing economics outcomes of conservation and crop production. Understanding these outcomes requires quantifying economics of crop production and conservation enrollment. Precision agriculture technology provides a mechanism to address these needs by using advanced technology to quantify spatially explicit profitability in agricultural fields. Precision agriculture's application to conservation planning represents a growing field of research. I present a brief overview of precision agriculture technology and its application in natural resource conservation. I discuss the role precision agriculture can play in United States conservation policy, highlight hindrances to adopting this technology, and provide recommendations for future application. I outline a new approach of targeted conservation delivery that focuses on return on investment to agricultural producers and discuss the role of precision agriculture in this approach. Increased adoption and application of this technology in natural resource conservation will require substantial investment from state wildlife agencies, nongovernmental organizations, farm managers, rural banks, and agricultural companies. Precision agriculture represents the next paradigm shift in natural resource conservation where spatially explicit conservation decisions are made that optimize conservation and profitability to produce environmentally resilient, multifunctional agricultural landscapes. © 2019 The Wildlife Society.